The Role of Tax Morale as Mediator in The Relationship between Religiosity and Tax Compliance in South Sumatra - Mareska Nurani; Imas Nurani Islami (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2020)
The aims of this study is to examine the direct effect of religiosity on taxpayer compliance level. Besides, this study also examines the indirect effect of religiosity on taxpayer compliance using the mediation variables of taxpayer morale. The data were gathered survey method that was able to collect as much 160 samples that can be used for analysis. The validity and reliability of instruments test were conducted before testing the hypothesis. The indirect influence was calculated from Variance Accounted For (VAF) mediating model. The result showed that the level of religiosity has a positive effect on tax morale and taxpayer compliance. High tax morale would increase taxpayer compliance. The results also provided empirical evidence that there was an indirect influence of religiosity on taxpayer compliance through the mediation of tax morale.